แบบจำลอง 2 มิติ สถานะชั่วครู่เพื่อทำนายแนวโน้มของอุณหภูมิที่ผนังท่อความร้อน - ศิริวรรณ นรินทร์; กาญจนวนิชกุล เกียรติสิน; ชมพูคำ ธีรพัฒน์; ฤทธิเดช สัมพันธ์ (RMUTP Research Journal Sciences and Technology, 2014)
Distribution trend of transient temperature profile of copper heat pipe from the start-up of outer wall temperature of evaporator section until the temperature was steady was studied. A two-dimensional model used numerical solution which based on finite difference method. The transient temperature distributions measured in all 3 heat pipe sections were compared with results from the numerical solution of the two-dimensional model that utilized the concept of temperature distribution in the pipe wall during transient operation. Results showed that the experimental trend and the theoretically predicted temperature profiles were similar. Moreover, there was good agreement when compared with the numerical simulation of Mistry et al. (2010). Therefore, the numerical-validated heat pipe temperature distributions were successfully simulated in a two-dimensional model.